Politik Hukum Agraria untuk Hak Atas Tanah Ulayat bagi Pemenuhan HAM dan Kepentingan Publik - Murni, Hidayati; Nelson, Febby Mutiara (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The political direction of agrarian law with regard to customary law and customary rights (beschikkingsrecht) of indigenous peoples during the Dutch colonial period wanted to unify and codify land law that applied to all groups of people based on the principle of concordance, but failed miserably, so that the pluralism policy was still applied. The current problem is in contemporary Indonesia, so it can be predicted that the prospect of pluralist customary rights of indigenous peoples must be maintained because it is in line with the mandate of the constitution in the upcoming reform era in the face of globalization by combining with efforts to reform agrarian law and land law through research on the political direction of customary rights law for the fulfillment of human rights or the public interest, The research method used by the author to conduct research is Juridical Nomaritf, the results of research in this study need to be followed up by mapping customary rights according to the rules of Geodesy, so that it is clear the extent of customary rights areas in the archipelago and ultimately can contribute to supporting the existence and legal certainty of customary rights in particular and land law for the public interest which will provide fulfillment of human rights.